Europe's building stock and its energy demand: A comparison between Austria and Italy. - Pezzutto, Simon; Haas, Franziska; Exner, Dagmar; Zambotti, Stefano (Springer, 2018)
The building sector is responsible for approximately 40% of the European Union s total primary energy demand, which is mainly attributed to space heating, cooling and domestic hot water. In 2010, its value reached 1800 Mtoe/y, to which buildings contributed 720 Mtoe/y. While the Austrian and Italian building stocks are well investigated (e.g., classified by different building typologies, existing floor area, ownership etc.), there still is a lack of information concerning energy/demand values for space heating, cooling and domestic hot water per the various construction periods. In order to identify differences in energy demand, we first classified residential and service sector buildings in Austria and Italy and then attributed specific demand values in kWh/m2 year. We further subdivided existing buildings per construction period: buildings (i) constructed before 1945, (ii) erected after World War II and before 1960, (iii) built between 1960 and 1980, (iv) constructed during 1980-1990 and 1990-2000, (v) dating to 2000-2010, and erected after 2010. The investigated buildings in the residential sector comprise: single-family houses, multi-family houses and apartment blocks (with more than eight floors); and in the service sector: offices solely. We concentrated our service-sector research on offices motivated by their highest space-cooling-demand ratio within the whole European building stock. The main results show that Austria and Italy share a certain homogeneity among building typologies, construction methodologies, portions of built-floor area per construction span, and specific energy demands per construction period.
Keywords: Energieverbrauch; Energieeinsparung; Energiebedarf; Gebäudebestand; Haustyp; Gebäudenutzung; Konstruktionsart; Gebäudealter